Labor epidural analgesia and risk of autism Spectrum disorders in offspring: A systematic review and meta-analysis - Fang, Ling-ling; Zhou, Yuan-yue; Jiang, Hai-yin; Shi, Yu-dan (Frontiers in Pediatrics, 2023)
Background The effect of labor epidural anesthesia (LEA) on the risk of autism spectrum disorder (ASD) in offspring has been investigated recently, and available results are inconsistent. Methods We searched the PubMed and EMBASE databases for relevant studies and performed a systematic review and meta-analysis of the literature. Subgroup analyses were conducted to assess the sources of heterogeneity. Both fixed and random effects models were used was used to estimate overall relative risk. Results Our results showed that LEA was associated with an increased risk of ASD in offspring [HR = 1.3, 95% confidence interval (CI): 1.25–1.35; P < 0.001] after combining crude estimates from the included studies. This association was gradually reduced, but still statistically significant, when potential confounding factors were considered (HR 1.13, 95% CI 1.03–1.25, P = 0.014). However, there was no significant association when we combined data of siblings from other pregnancies (HR = 1.07, 95% CI: 0.99–1.16, P = 0.076), implying that the association was due to confounding factors. Conclusion The statistically significant association between LEA and ASD in the offspring can be partially explained by unmeasured confounding. Systematic Review Registration Identifier CRD42022302892.